2011
DOI: 10.7863/jum.2011.30.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Systematic Approach in the Evaluation of Fetal Facial 3-Dimensional Volumes

Abstract: The benefits of using volume ultrasonography (3-dimensional ultrasonography [3DUS]) have been explored in diagnosing fetal anomalies 1-3 such as cleft lip and palate, 4-11 micrognathia, 12,13 congenital heart diseases, [14][15][16] and skeletal abnormalities. 17,18 However, clinical implementation of this new technology has been challenging for many reasons, including familiarity with the knobology and orientation within a volume of data. Training of physicians to use volume ultrasonography has been limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There have been a number of publications dealing with the potential superiority of 3D vs. 2D-based studies on facial integrity in normal and aneuploid fetuses [25][26][27][28]. It has been shown that the facial maxillary angle is significantly larger when assessed via a three-dimensional approach.…”
mentioning
confidence: 99%
“…There have been a number of publications dealing with the potential superiority of 3D vs. 2D-based studies on facial integrity in normal and aneuploid fetuses [25][26][27][28]. It has been shown that the facial maxillary angle is significantly larger when assessed via a three-dimensional approach.…”
mentioning
confidence: 99%
“…3DUS has been used over the last few years as a prenatal diagnostic technique complementary to 2DUS and has enabled better assessment of fetal surface abnormalities [11]. In our specific case, 3DUS clearly demonstrated the twisting and absence of some toes.…”
Section: Discussionmentioning
confidence: 70%
“…Ramos et al 92 found that: use of three-dimensional ultrasound for visualization of the profile took about 60 seconds and about 73 seconds for the primary palate; that this period might be shorter in expert hands; and a standardized teaching program might improve the use and accuracy of bi-dimensional 93 and three-dimensional ultrasound. 92 However, there are no statistics permitting a precise comparison of the financial aspects of the two approaches.…”
Section: Discussionmentioning
confidence: 99%